(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article provides a route system for city bus stops. In this article, it is necessary to ensure the normal quality of the work of urban passenger transport, as well as to choose the exact and normative growth of buses and take into account the conditions for their regular operation. Fuel savings on buses can reduce costs for businesses. The demand for passenger transport is growing, taking into account the expansion and development of the city. However, there are also problems with the provision of transport services to the population. Passenger transportation is aimed at improving the quality of service. Ecology also aims to reduce exhaust emissions.